Analisis Economic Of Scale Dan Efisiensi Penggunaan Input Terhadap Output Pada Industri Genteng Di Kecamatan Kediri Kabupaten Tabanan - Sri Handayani, Ida Ayu Putu; Purbadharmaja, Ida Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 8, No. 5, Mei 2019, pp (945-1180), 2019)
The most developed industry in Tabanan district is the tile industry located in Kediri Subdistrict, but the development of its production value has decreased. This study purpose to determine the influence of raw material, fuel energy and labor on production partially and simultaneously and how the economic of scale and efficiency of industrial production of tile in Kecamatan Kediri Tabanan regency. Analyzer used is multiple linear regression with double log model. Result of analysis indicate that variable of raw material, energy of fuel and labor simultaneously and partially have positive and significant influence to production amount in tile. Economy scale of tile partially or simultaneously decreasing return to scale because the amount of regression coefficient from each input value 0, 946 <1. Efficiency from the use of input tile industry are in inefficient condition because the efficiency of each input value <1. The use of production factors should be used proportionally to achieve efficient conditions.